2022
DOI: 10.1002/ece3.8338
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intraspecific competition and body mass on diet specialization in a mammalian scavenger

Abstract: Dietary specialization is a known predictor of population decline, leading certain species to become more vulnerable to threat of ex-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 109 publications
0
10
0
Order By: Relevance
“…
Figure 5 Posterior plot of the estimated diet composition of devils living in four habitats with differing anthropogenic impacts (cleared land, wet eucalypt-other, wet eucalypt-rainforest, rainforest). Five potential food groups were included in the mixing model based on Lewis et al 54 : Tasmanian pademelon/European hare; brushtail possum; red-necked wallaby; green rosella; and other birds (black currawong; laughing kookaburra; and masked lapwing). Mean proportions, standard deviations and 95% CIs are included in Supplementary Table 5 .
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…
Figure 5 Posterior plot of the estimated diet composition of devils living in four habitats with differing anthropogenic impacts (cleared land, wet eucalypt-other, wet eucalypt-rainforest, rainforest). Five potential food groups were included in the mixing model based on Lewis et al 54 : Tasmanian pademelon/European hare; brushtail possum; red-necked wallaby; green rosella; and other birds (black currawong; laughing kookaburra; and masked lapwing). Mean proportions, standard deviations and 95% CIs are included in Supplementary Table 5 .
…”
Section: Resultsmentioning
confidence: 99%
“…Rainforest-living devils had a comparatively broad isotopic niche and showed some evidence of partitioning, with heavier individuals having higher nitrogen stable isotope values than their smaller counterparts. Primary consumers in the Tasmanian isoscape do not all feed at the same nitrogen isotope ratio 54 . Instead, the higher nitrogen values found in heavier devils indicate that they were feeding primarily on medium-sized herbivorous mammals, while the lower values of smaller devils imply a diet of herbivorous birds 54 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…As Bolnick et al (2003) and a number of more recent studies on various animals ( Bolnick et al, 2007 ; Araújo, Bolnick & Layman, 2011 ; Lucas et al, 2018 ; Szigeti et al, 2019 ; Lewis, Hughes & Rogers, 2022 ) demonstrated, there are two fundamentally different ways to be a dietary generalist. Either all individuals in a population are generalised, or different individuals specialise on different resources, as we found in Ceratina bees.…”
Section: Discussionmentioning
confidence: 99%